An 11-year-old boy with pharyngitis and cough: Lemierre syndrome. (23rd April 2013) - Mação, Patricia; Cancelinha, Candida; Lopes, Paulo; Rodrigues, Fernanda
Abstract : The authors present the case of an 11-year-old boy with pharyngitis, treated with amoxicillin, that worsened on day 7, with cough, high fever and refusal to eat. Lethargy and respiratory distress were noted. Based on radiographic findings of bilateral infiltrates he was diagnosed with pneumonia and started on intravenous ampicillin and erythromycin. Two days later he complained of right-sided neck pain and a palpable mass was identified. An ultrasound showed partial thrombosis of the right internal jugular vein and a lung CT scan revealed multiple septic embolic lesions. Lemierre syndrome was diagnosed, antibiotic treatment adjusted and anticoagulation started. A neck CT-scan showed a large parapharyngeal abscess. His clinical condition improved gradually and after 3 weeks of intravenous antibiotics he was discharged home on oral treatment. This case illustrates the importance of diagnosing Lemierre syndrome in the presence of pharyngitis with localised neck pain and respiratory distress, to prevent potentially fatal complications.